Super-sized slugger : a novel - Ripken, Cal, Jr., 1960- (Ripken, Cal, Jr., 1960- Cal Ripken, Jr.'s all-stars., 2012)
Thirteen-year-old Cody Parker moves to Baltimore, Maryland, where as a fat eighth-grader, he has to deal with brutal teasing from a baseball teammate, and his school is beset by a rash of mysterious thefts that threaten to sideline Cody and ruin a golden season for his team.